From a "Garden of Disorder to a "Nest of Flames": Charles Henri Ford's Surrealist Inflections (Miranda: Revue pluridisciplinaire du monde anglophone, 2017)
Virtually omitted from established narratives of American modernism, yet central in the histories of the reception of European Surrealism in the US, Charles Henri Ford’s life and work have been recovered in important queer genealogies within Anglo-American modernism. Yet within this process or recovery, Ford’s poetic work is still largely overlooked, and this may have to do less with its marked Surrealist influences and/or derivative aspects than with the somewhat unclassifiable and composite texture of Ford’s poems. This article revisits Ford’s early poetry as a space of convergence and dialogue between distinct yet interrelated poetics: from the 1938 A Garden of Disorder to the 1949, Sleep in a Nest of Flames, a queer subjectivity assimilates concurrently Surrealist poetics and Djuna Barnes’s equally unclassifiable queer modernism with and against American poetic modernisms.